THE CONCEPT OF TRANSCENDENTAL LOVE IN THE TAFSĪR AL-QURĀN AL-AẒĪM BY AT-TUSTURIY - Hakki Akmal Labib (Teosofia: Indonesian Journal of Islamic Mysticism, 2018)
Abstract The concept of ḥhubb is closely related to daily life. Anyone must have love. Whether it's love from biological aspect, social aspect, or theological aspect. This is one of the reasons why researchers choose the term ḥhubb. And the other reasons are, first, the word ḥhubb is one of the key words in al-Qurān that describes the concept of deed, whether it is the concept of worship, as well as the social concept beloved by God and it is important to be known as the sustainer of everyday life. Secondly, the translation of al-Qurān gives only the earliest description of the meaning of the word ḥhubb only to the extent of the meaning of love, thus requiring a deeper explanation in order to know its meaning comprehensively. So, this study will discuss about the concept of ḥhubb according Sahl bin ‘Abdullāh at-Tusturī in Tafsīr al-Qurān al-Aẓīm. He was known by a mutaṣawwīf and mufassīr